Wild-type but not mutant huntingtin modulates the transcriptional activity of liver X receptors. Issue 7 (17th May 2009) - Futter, M; Diekmann, H; Schoenmakers, E; Sadiq, O; Chatterjee, K; Rubinsztein, D C
Abstract : Background: Huntington's disease is caused by expansion of a polyglutamine tract found in the amino-terminal of the ubiquitously expressed protein huntingtin. Well studied in its mutant form, huntingtin has a wide variety of normal functions, loss of which may also contribute to disease progression. Widespread transcriptional dysfunction occurs in brains of Huntington's disease patients and in transgenic mouse and cell models of Huntington's disease. Methods: To identify new transcriptional pathways altered by the normal and/or abnormal function of huntingtin, we probed several nuclear receptors, normally expressed in the brain, for binding to huntingtin in its mutant and wild-type forms. Results: Wild-type huntingtin could bind to a number of nuclear receptors; LXRα, PPARγ, VDR and TRα1. Over-expression of huntingtin activated, while knockout of huntingtin decreased, LXR mediated transcription of a reporter gene. Loss of huntingtin also decreased expression of the LXR target gene, ABCA1. In vivo, huntingtin deficient zebrafish had a severe phenotype and reduced expression of LXR regulated genes. An LXR agonist was able to partially rescue the phenotype and the expression of LXR target genes in huntingtin deficient zebrafish during early development. Conclusion: Our data suggest a novel function for wild-type huntingtin as a co-factor of LXR. However, this activity is lost by mutant huntingtin that only interacts weakly with LXR.